Compare the Effectiveness of Clinic-Based Rehabilitation and On-Field Training in Patients with ACL Injuries - Deora, Veer Singh; Pinjara, Farukh Mohammad; Khan, Usman; Khan, Jafar; Lohar, Deepak; Pal, Renuka; Katariya, Hirendra Kumar; Jaini, Preksha; Bhatnagar, Suhani; Kania, Vaishnavi (Journal of Neonatal Surgery, 2025)
Background: Anterior cruciate ligament (ACL) injury is a common knee injury in athletes and active individuals. Rehabilitation is critical to restore function and reduce re-injury risk. Two common rehabilitation approaches are structured clinic-based rehabilitation (CBR) and progressive on-field training (OFT). This study compares the effectiveness of CBR and OFT in improving patient-reported outcomes, functional performance, and return-to-sport (RTS) rates. Need of study: The demand for a comprehensive, evidence-based approach to anterior cruciate ligament (ACL) rehabilitation has grown substantially in recent years, largely due to the increasing prevalence of ACL injuries and the varied outcomes associated with different recovery pathways Objective: To compare clinical outcomes, functional performance, return-to-sport rates, and re-injury incidence between clinic-based rehabilitation and on-field training in patients following ACL reconstruction (ACLR). Methods: This single-center, parallel-group randomized controlled trial enrolled 40 patients aged 16–40 years who underwent primary ACLR. Participants were randomized 1:1 to CBR or OFT. Primary outcome: International Knee Documentation Committee (IKDC) subjective knee evaluation score at 12 months. Secondary outcomes: Knee Injury and Osteoarthritis Outcome Score (KOOS), Lysholm score, isokinetic quadriceps/hamstring strength, single-leg hop tests, time to RTS, and re-injury rate at 24 months. Results: (summary): Both groups improved significantly from baseline. At 12 months, mean IKDC scores were similar between groups (CBR: 85.2 ± 8.1; OFT: 86.5 ± 7.6; mean difference 1.3, 95% CI -1.8 to 4.4, p=0.41). Time to unrestricted RTS was shorter in the OFT group (median 8.5 months vs 9.6 months, p=0.03). Re-injury rates at 24 months were not significantly different (CBR 6.7% vs OFT 8.3%, p=0.72). Functional hop tests and strength symmetry showed comparable outcomes. Conclusion: Clinic-based rehabilitation and progressive on-field training produce similar patient-reported outcomes and functional recovery at 12 months. On-field training may accelerate time to return to sport without increasing short-term re-injury risk. Further multicenter studies with longer follow-up are warranted.